2013
DOI: 10.1523/jneurosci.4149-12.2013
|View full text |Cite
|
Sign up to set email alerts
|

PrPCControls via Protein Kinase A the Direction of Synaptic Plasticity in the Immature Hippocampus

Abstract: The cellular form of prion protein PrP C is highly expressed in the brain, where it can be converted into its abnormally folded isoform PrP Sc to cause neurodegenerative diseases. Its predominant synaptic localization suggests a crucial role in synaptic signaling. Interestingly, PrP C is developmentally regulated and its high expression in the immature brain could be instrumental in regulating neurogenesis and cell proliferation. Here, PrP C -deficient (Prnp 0/0 ) mice were used to assess whether the prion pro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
29
0
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
5
2
2

Relationship

0
9

Authors

Journals

citations
Cited by 42 publications
(31 citation statements)
references
References 47 publications
1
29
0
1
Order By: Relevance
“…A wealth of studies explored the functional aspects of this interaction, suggesting that PrP C may act as a copper transporter, a sink of copper excess or a scavenger for free radicals [13,14]. These findings are consistent with current evidence proposing a PrP C neuroprotective function [15][16][17].…”
Section: Introductionsupporting
confidence: 80%
“…A wealth of studies explored the functional aspects of this interaction, suggesting that PrP C may act as a copper transporter, a sink of copper excess or a scavenger for free radicals [13,14]. These findings are consistent with current evidence proposing a PrP C neuroprotective function [15][16][17].…”
Section: Introductionsupporting
confidence: 80%
“…We also measured the level and the activity-dependent phosphorylation of CaMKII, cAMP-dependent protein kinase (PKA), and extracellular signal-related kinase 1/2 (ERK1/2), which are involved in dendrite remodeling (Hudmon and Schulman, 2002;Caiati et al, 2013;Silingardi et al, 2011). The results showed that the level of phosphorylated CaMKII at Thr286 (pCaMKII) was remarkably increased in hippocampus of T-hHcy rats, whereas the levels of total CaMKII, total ERK1/2 and pERK1/2, PKAa catalytic subunit (PKAa-cat), and PKA Ib regulatory subunit (PKA Ib-reg) were not changed by training (Fig.…”
Section: Camkii Activation Mediates the Training-induced Ameliorationmentioning
confidence: 99%
“…Recent research demonstrates that PrP c is involved in synaptic plasticity processes in the neonatal hippocampus (33). In addition, PrP c has been proposed as an additional possible mediator of oligomer action.…”
Section: Aβ-relevant Receptors Involved In Regulating Synaptic Plastimentioning
confidence: 99%